2018
DOI: 10.1590/1809-4430-eng.agric.v38n3p309-318/2018
|View full text |Cite
|
Sign up to set email alerts
|

Protected Environments and Substrates for Achachairu Seedlings

Abstract: The Achachairu (Garcinia humilis) is a Bolivian exotic fruit that has been produced and commercialized a few years in Brazil. Information about the production of high quality seedlings is essential for the implementation and the renewal of orchards. The objective was to evaluate protected environments and substrates for Achachairu seedlings. Two protected environments were evaluated, one covered with aluminized thermal reflector screen of 50% of shading and the other with Sombrite® of 50% of shading. Inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
11
2
1
Order By: Relevance
“…In the same way Costa et al (2012) studying Tamarindus indica reported a relationship between substrate and DQI. Contrasting our results Silva et al (2018) did not find significant differences for DQI in Achachairu (Garcinia humilis) seedlings grown in different substrate compositions, the authors attributed this result to the adaptability of the seedlings in high quality substrates.…”
contrasting
confidence: 99%
“…In the same way Costa et al (2012) studying Tamarindus indica reported a relationship between substrate and DQI. Contrasting our results Silva et al (2018) did not find significant differences for DQI in Achachairu (Garcinia humilis) seedlings grown in different substrate compositions, the authors attributed this result to the adaptability of the seedlings in high quality substrates.…”
contrasting
confidence: 99%
“…In the production of G. humilis seedlings, Silva et al (2018) compared two production environments with 50 % shading screens and showed that the nursery with aluminized thermal-reflective screen resulted in more vigorous seedlings with a higher dry matter of shoots and roots, when compared to the nursery with black shading screen. Studies with sunlight restriction levels for forest tree species have reported that the 50 % shading level resulted in high-quality seedlings for Schizolobium amazonicum Huber ex Ducke (Gondin et al 2015), Caesalpinia ferrea C. Mart.…”
Section: Introductionmentioning
confidence: 99%
“…Materials from organic or mineral sources are easy to acquire and have a good porosity to provide physicochemical properties essential to the requirements of each species. According to Silva et al (2018), the use of substrate based on the mixture of cattle manure, soil, vermiculite and sand is adequate to produce G. humilis seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary results were reported in achachairu seedlings (Garcinia humilis Vahl.) by Silva et al (2018), who showed that nursery with aluminized thermal-reflective screen produced better quality seedlings when compared to the nursery with black shading screen.…”
Section: Resultsmentioning
confidence: 99%
“…The production of seedlings in protected environments can improve the quality and sanity of the plants due to the improvement of environmental conditions such as temperature, humidity, and light intensity during all seasons of the year. Silva et al (2018) studied the initial growth of achachairu seedlings (Garcinia humilis Vahl.) in two production environments with 50% shading, showed that nursery with aluminized thermal-reflective screen produced better quality seedlings when compared to the nursery with black shading screen.…”
Section: Introductionmentioning
confidence: 99%